Pengembangan Multimedia Interaktif Berbasis Articulate Storyline pada Pokok Bahasan Klasifikasi Materi dan Perubahannya untuk Peserta Didik SMPN 2 Maros Kelas VII - Rina Yusrina; Firdaus Daud; Muhammad Danial (Universitas Negeri Makassar, 2022)
This study is a development research (Research & Development) which aims to produce an interactive multimedia product based on Articulate Storyline which is valid, practical, and effective and to analyze the level of validity, practicality, and effectiveness as well as the relationship between the practicality and effectiveness on the development of Articulate Storyline-Based Interactive Multimedia in the Material Classification and Its Changes Subject for Grade VII students at SMPN 2 Maros. The study employed ADDIE development model, which included five stages of activities, namely analysis, design, development, implementation, and evaluation. This research was conducted at SMPN 2 Maros with research subjects namely students of grade VII A with 30 people and teachers of science subject with 27 people. The research instruments used were interactive multimedia validation sheets based on Articulate Storyline, teachers’ response questionnaires and students’ response questionnaires, as well as test instruments in the form of multiple choice questions. Data on the level of validity and practicality were collected using questionnaires and data on the level of effectiveness employed learning outcomes test. Based on the analysis results of interactive multimedia validity data based on Articulate Storyline developed, it has an average value of 4.7 which is in valid category. The results of the teacher's response questionnaire obtain a total average score percentage of 88.90 with a very positive response category and the students’ responses obtain a total average score percentage of 83.90 with a very positive response category. The percentage of students passing is 90, which is in effective category. Therefore, it can be concluded that the interactive multimedia based on Articulate Storyline which was developed using the ADDIE model, has met the valid, practical, and effective categories.